Construction and Efficiency of Aluminum Cans Shredder Machine - Thongkup, Weraphol; Phomkaew, Krissada; Sarapab, Srongyot; Wanriko, Amnard (Princess of Naradhiwas University Journal, 2020)
The objective of this research was to construct and find the efficiency of the aluminum can shredding machine by using the theory of torsion. The efficiency of aluminum cans shredder machine was evaluated by shredding of aluminum cans with net content of 140 ml at 15 kg, with the time of shredding at 37.51 min and shredding size of 31.20 mm, 230 ml of 15 kg, with the time of shredding at 39.53 min and shredding size of 31.23 mm, 320 ml of 15 kg, with the time of shredding at 40.32 min and shredding size of 31.44 mm, and 490 ml of 15 kg, with the time of shredding at 41.29 min and shredding size of 31.42 mm, using blade speed of 28.60 rpm. The assessment evaluation was done by 15 experts that from 9 mechanical experts and 6 aluminum recycling experts: The design and structure was high quality level at 4.31. The material selection was good quality level at 4.36 and the use of aluminum cans shredding machine was very good quality level at 4.39.